Peran Ayah dalam Pembinaan Karakter Anak Kajian terhadap Pola Asuh di Komunitas Home Education Aceh - Irma Yunita (Ar-Raniry: International Journal of Islamic Studies, 2019)
The role of the father has a very important position in the development of children's education and character. However, it is very unfortunate that this paradigm has not been taken seriously, especially by some of the authorities in the world of education, including some parents. The presence of the Aceh Home Education community is to minimize this condition, by inviting parents, especially fathers, to return to their function as the main educators in the family. The focus of this study aims to analyze the role of fathers and parenting patterns in fostering children's character and the obstacles faced by fathers in fostering children's character in the HEA community. This type of research is qualitative research, using a descriptive analysis approach. The data collection techniques through interview and documentation instruments. The subjects in this study were community elements which included the HEA Coordinator and members of the HEA community, namely three fathers and three mothers, with the main subject being the father. Data analysis uses data reduction techniques, data display and conclusion. The results of the data analysis show that: (1) the role of the father in the HEA community has reached indicators, such as the presence of each father in the family in guiding children and family members. (2) The parenting style carried out by fathers has met the indicator requirements, such as democratic parenting, exemplary and others. (3) And almost no significant obstacles have been found in the process of developing children's character.